Pengaruh Beban Kerja Terhadap Kinerja Pramugraha: Studi Kasus Di Marbella Suites Bandung - Kalsum, ER Ummi (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
This research is associative research with a causal relationship based on the explanation level, that is how this research is explained. Associative research is research in which the aim is to find a relationship or influence between two or more variables that serve to explain, predict and control certain symptoms. While the causal relationship is the cause-effect relationship, where X Influences Y. This research when viewed from the goal is applied research or applied research, which is "research that aims to obtain discoveries related to the application of certain theories" This research is practical by testing theory in the face of real problems in certain situations. The results of this study note that the workload of pramugraha in Marbella Suites Bandung needs to be re-examined so that the workload delegated to pramugraha more optimal. The individual workload of the pramugraha who is still in severe condition indicates an imbalance in the workload. Of the 15 questions based on 10 workload indicators, there are 13 aspects that are still in the weight category, while the other 3 are in enough category. The heaviest dimension according to the pramugraha response is the state of the room followed by productive time, productivity level, and type of work. However, the dimension of productive time has a greater effect on performance compared to other workload dimensions. The dimensions of work, the state of the room, and the level of productivity follow in a row in affecting the performance of pramugraha at Marbella Suites Bandung. Performance pramugraha Marbella Suites Bandung is in the bad category which means that the performance of pramttgraha should be optimized for pramugraha productivity can be better. There are 5 out of 10 indispensable indicators of communication skills, how the work is done, the discipline, the outcomes of work, and how the work is done. The other, five indicators are sufficiently categorized, namely loyalty, reliability, leadership, service to guests, and multicultural governance. The most severe dimensions based on pramugraha responses are objective results followed by behavior and personality. Delivered workloads contribute significantly to the performance of pramugraha at Marbella Suites Bandung. The performance of pramugraha will adjust to the workload carried by the steward. Workload affects performance by 59%. Based on table 4:40 about the correlation between workload with pramugraha performance in Marbella Suites Bandung, the effect of workload load on performance is 0.767 which means that there is a strong influence between two variables positively and significantly. So it can be concluded that the influence of workload on pramugraha performance in Marbella Suites Bandung is 59% and 41% other influenced by other factors outside the workload. This shows a strong correlation between workload and pramugraha performance in Marbella Suites Bandung.